Treatment of Lowland Frogs From the Spawn Stage with Homeopathically Prepared Thyroxin (10-30) - Helmut Graunke; P. Christian Endler; Waltraud Scherer-Pongratz; Heinz Spranger; Michael Frass; Harald Lothaller (The Scientific World Journal)
The influence of a highly diluted agitated, i.e. homeopathically prepared thyroxin solution (10-30, final concentration in the basin water 10-35 parts by weight after the first application) on metamorphosis in lowland Rana temporaria from the spawn stage on was studied. The treatment with homeopathically prepared thyroxin solution (10-30) starts at the frogspawn stage. It represents a tool to learn more about the previously standardized amphibian model, where the thyroxin solution was applied from the two- legged stage on only. Lowland frogs were pretreated by immersing spawn in an aqueous molecular thyroxin dilution (10-8 parts by weight). In later stages of development (2 to 4 legged), this has been found to speed up metamorphosis by around 15%. In accordance with the homeopathic idea of detoxication or cure, hyperstimulated animals (spawn or, in subsequence, larvae) were treated either with thyroxin that had been highly diluted and agitated in successive steps, i.e. homeopathically prepared (10-30), or analogously prepared blank solution (water). Development was monitored by documenting the number of animals that had entered the four-legged stage. It has been found that animals treated with the test solution metamorphosed more slowly than the control animals, i.e. the effect of the homeopathically prepared thyroxin was opposed to the usual effect of molecular thyroxin. The number of test animals that reached the 4- legged stage at defined points in time was slightly smaller in the group treated with homeopathically prepared thyroxin at some, but not at all points in time, compared to control. The results in this study sustain the previous multi researcher findings that highly diluted homeopathically prepared thyroxin is able to slow down metamorphosis of Rana temporaria.